Methodical Investigation of Cognitive Domain of Dairy Farmers on the Practice of Mineral Mixture Supplementation and Its Interaction with Socio-personal Characters - Hundal, Jaspal Singh; ., Aparna; Singh, Udeybir; Bhatti, Jaswinder Singh (Indian Journal of Animal Nutrition, 2018)
This study was conducted in Roopnagar and Patiala districts of Punjab state in order to assess the level of adoption and knowledge of farmers on mineral mixture and interaction of these factors in defining the level of knowledge. A total of 137 farmers were randomly selected and data were collected with a pretested questionnaire and knowledge test through an interview schedule. The results indicated that 22.62% farmers have adopted the technology of supplementing mineral mixture and 21.46% have adopted it partially. About71.53% respondents used calcium supplements with or without mineral mixture. About 45.3% respondents had low level, 15.3% respondents had medium and 39.4% farmers had a high level of knowledge regarding use of mineral mixture. Approximaely, 50.4% farmers knew that mineral mixture has to be fed by mixing with concentrate mixture while only 10.9% knew that it can be mixed with green fodder too. About 9-16% respondents had the knowledge on categories of animals to be fed mineral mixture. 11-19% respondents had the knowledge that mineral mixture can positively affect milk production. However, awareness on deficiency symptoms like anoestrous, abortion, pica, indigestion and prolapse was as high as 48%. Higher education, bigger herd size, more frequent use of information sources, training and contact with extension agents affected (P